Ways of regulating inner-city conflicts - the example of the moderation process of the cooperation process in the city center of Freystadt/Upper Palatinate - Maier Jörg (Journal for Geography, 2012)
The paper describe the example of urban management activities as a result of the program for revitalisation of the town center. The problem occures after the decision of trade company to built up a new shopping center on the edge of the town. The result of this decision could be the loss of attractivnes of the town center. The retailers and caterers togeather with state support and experts have prepared the program for better and more attractive offer in town centre.